Georgia Architectural and Historic Properties Survey of 403 Summerlin St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 403 Summerlin St., Valdosta, Ga., December 1980. Shotgun house with gabled roof, shed porch with square posts. Shiplap siding. Double hung sash windows with 6/6 lights. Set on brick piers. Poor condition. Date of Construction: N/A.
Georgia Architectural and Historic Properties Survey of 403 Summerlin St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 0 photograph. 52.5 MB (55,069,032 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)